1979
DOI: 10.1021/bi00590a025
|View full text |Cite
|
Sign up to set email alerts
|

Increased thermal stability of proteins in the presence of sugars and polyols

Abstract: Sugars and polyols stablize proteins against heat denaturation. Scanning calorimetry was used to obtain a quantitative estimate of the degree of stabilization. Solutions of ovalbumin, lysozyme, conalbumin, and alpha-chymotrypsinogen were heated at a constant rate, and the temperature of the maximum rate of denaturation was estimated (Tm). Addition of a sugar or polyol raised Tm. The magnitude of the stabilizing effect (delta Tm) depended on both the nature of the protein and the nature of the sugar or polyol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
381
1
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 733 publications
(400 citation statements)
references
References 32 publications
17
381
1
1
Order By: Relevance
“…A comparatively high value of ⌬T m of 18.2°C (⌬G 0 ϳ 4.5 kcal mol Ϫ1 ) for RNase A at 2 M concentration of trehalose and pH 2.5 is indicative of this (Table I). This increase is much higher compared with any other sugar or polyol studied in the literature (5,19,25). The magnitudes of ⌬T m at other pH values for RNase A as well for several other proteins are also significantly higher.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A comparatively high value of ⌬T m of 18.2°C (⌬G 0 ϳ 4.5 kcal mol Ϫ1 ) for RNase A at 2 M concentration of trehalose and pH 2.5 is indicative of this (Table I). This increase is much higher compared with any other sugar or polyol studied in the literature (5,19,25). The magnitudes of ⌬T m at other pH values for RNase A as well for several other proteins are also significantly higher.…”
Section: Discussionmentioning
confidence: 70%
“…Sugars have been known to protect proteins against loss of activity (1, 2), chemical (3,4), and thermal denaturation (5)(6)(7)(8)(9). Among several sugars, ␣,␣-trehalose (␣-D-glucopyranosyl(131)-␣-D-glucopyranoside) has been known to be a superior stabilizer in providing protection to biological materials against dehydration and desiccation (10,11).…”
mentioning
confidence: 99%
“…If some of the protein charge sites are still isolated and the solvent molecules are able to provide counter ions to yield a neutral surface. Beyond these advantages features, glycerol is well known to stabilize folded protein structures [15].…”
Section: Efficiency Of Soft-landing For Different Substratesmentioning
confidence: 99%
“…However, retention of the biological activity of a protein or other biomolecule in the course of this (or any mass spectrometry experiment) is a much more challenging problem. This is the subject addressed in the present paper through the combined choice of gentle ionization methods and an appropriate liquid surface for soft-landing.It is well known that polyols and sugars can efficiently stabilize a protein in an otherwise denaturating environment [15,16], although the underlying mechanism of this process has not been elucidated. Lakshmi and Nandi [17] in 1976 showed that sucrose and glucose decrease the solubility of phenylalanine, tyrosine, and tryptophan in aqueous solution and suggested that this was due to increased hydrophobic interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation